2007
DOI: 10.1136/gut.2007.121616
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental role for CD4+ T lymphocytes in murine diffuse peritonitis due to inhibition of local bacterial elimination

Abstract: In diffuse peritonitis caused by commensal gut bacteria the CD4(+) T lymphocytes exert a net negative effect on the local anti-bacterial defence, and thereby contribute to bacterial dissemination and poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
5
20
1
Order By: Relevance
“…Cecal ligation and puncture (CLP) and colon ascendens stent peritonitis (CASP) are well-accepted IAI models that both involve a surgical procedure in which the cecum is perforated to release the cecal contents into the normally sterile peritoneal cavity. Studies using these models reported TNF-␣, IL-6, and IL-1␤ in the peritoneal lavage fluid and serum after surgery, albeit with different kinetics from those in our model (38,(47)(48)(49)(50)(51). Differences are likely attributed to the continuous leakage of diverse bacterial species from the cecum of mice that have undergone CLP or CASP, compared to the bolus injection of organisms used in our model.…”
Section: Discussioncontrasting
confidence: 38%
“…Cecal ligation and puncture (CLP) and colon ascendens stent peritonitis (CASP) are well-accepted IAI models that both involve a surgical procedure in which the cecum is perforated to release the cecal contents into the normally sterile peritoneal cavity. Studies using these models reported TNF-␣, IL-6, and IL-1␤ in the peritoneal lavage fluid and serum after surgery, albeit with different kinetics from those in our model (38,(47)(48)(49)(50)(51). Differences are likely attributed to the continuous leakage of diverse bacterial species from the cecum of mice that have undergone CLP or CASP, compared to the bolus injection of organisms used in our model.…”
Section: Discussioncontrasting
confidence: 38%
“…We reported recently that depletion of CD4 ϩ cells in mice subjected to CASP results in a strongly increased invasion of granulocytes and monocytes into the peritoneal cavity, leading to reduced bacterial numbers in peritoneal lavage fluid, blood, and all examined organs. This dampening effect of CD4 ϩ cells on the innate immune response could be shown to be detrimental for the survival of severe sepsis (15). As the migration of CD4 ϩ Foxp3 ϩ Tregs into nonlymphoid organs, e.g., liver and lung, is associated mainly with the expression of CCR4 (58), it may be concluded that absence of CCR4 leads to a reduced extravasation of Tregs into nonlymphoid organs, resulting in a diminished repression of the local innate immune defense.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we could demonstrate a rapid loss of T cells in the thymus due to a massive apoptotic activity after CASPinduced polymicrobial sepsis (15). As this phenomenon is a strict consequence of the systemic infection caused by CASP, the diminished number of apoptotic cells in the thymus and the mesenteric lymph nodes of CCR4-deficient mice must be taken as a clear marker for significantly alleviated severity of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, work by Rajakaria et al [7] demonstrated that RAG-deficient mice exhibited an exaggerated peritoneal response to zymosan with increased PMN infiltration evident at 2 and 6 h accompanied by increased TNF-a and reduced IL-10 levels. Also, anti-CD3 antibody-mediated depletion of peritoneal T cells resulted in increased numbers of PMN and M/ in colon ascendens stent peritonitis [8] suggesting that peritoneal T cells may act to inhibit the response of the peritoneum to bacterial infection.…”
Section: Introductionmentioning
confidence: 99%